2019
DOI: 10.1111/clr.13399
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial on the efficiency of free‐handed, pilot‐drill guided and fully guided implant surgery in partially edentulous patients

Abstract: Objectives To compare the effectiveness of free‐handed (FH), pilot‐drill guided (PG) and fully guided (FG) implant surgery by means of the apical global deviation (AGD) in relation to the additional financial cost and time spent. Materials and methods Thirty‐three partially edentulous patients in need of ≥2 implants in the posterior maxilla were randomly allocated to one of the following treatment groups: FH, PG and FG. Eleven patients (mean age 57; eight females; altogether 26 implants) were treated by FH sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(98 citation statements)
references
References 24 publications
3
92
0
Order By: Relevance
“…In addition, this superiority was shown for anterior and posterior implants. Such observations confirm the advantage of the FG protocol in controlling all the steps of osteotomy and implant placement [7,9,15,16]. On the contrary, the inaccuracies of the PG and FH protocols were generally similar and tended to be approximately double the inaccuracies of the FG protocol.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In addition, this superiority was shown for anterior and posterior implants. Such observations confirm the advantage of the FG protocol in controlling all the steps of osteotomy and implant placement [7,9,15,16]. On the contrary, the inaccuracies of the PG and FH protocols were generally similar and tended to be approximately double the inaccuracies of the FG protocol.…”
Section: Discussionsupporting
confidence: 69%
“…Likewise, Vermeulen found the FG protocol to be more accurate than the FH protocol [19]. Further, several clinical studies reported that the PG protocol is associated with approximately double the errors of the FG protocol [16,20,21]. On the contrary, the PG protocol inaccuracy seemed comparable to the FH protocol, which could be due to the execution of most of the drilling steps and implant placement without the use of guides, leading to inevitable deviation of the drills and implant placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that all of the implants with a buccal shoulder position ( n = 3) presented ≥1 mm mid‐facial recession shows benefit of these recent innovations. Given that guided implant surgery is most accurate (Younes et al., 2018) and has a favourable cost–benefit ratio (Younes, Eghbali, De Bruyckere, Cleymaet, & Cosyn, 2019), clinicians should at the very least consider guided implant surgery for IIP in order to avoid mid‐facial recession. Besides a buccal shoulder position, descriptive statistics also identified the lack of a CTG as putative risk factor for ≥1 mm mid‐facial recession.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on the accuracy of the full protocol, and their results indicate that full guidance yields higher accuracy than lower levels of guidance (Tahmaseb et al, 2014(Tahmaseb et al, , 2018Van Assche et al, 2012), though the difference is not always significant (Kühl et al, 2013). Less attention has been paid to the pilot and partial protocols and freehand surgery (Di Giacomo, Cury, Araujo, Sendyk, & Sendyk, 2005;Vercruyssen et al, 2015Vercruyssen et al, , 2014Younes, Eghbali, Bruyckere, Cleymaet, & Cosyn, 2019), even though the former are widespread, and the latter is still considered to be the standard by many. The accuracy of tooth-supported guides for partial edentulous cases (Arisan, Karabuda, & Ozdemir, 2010) is another under-discussed aspect, while it is safe to assume that partial edentulousness is a frequent reason for dental implantation.…”
Section: Introductionmentioning
confidence: 99%